TIG torch technique for hard face surfacing - Maleque, Md. Abdul (2018)
The hard face surface layers have been developed on alloy steel material by preplacing hybrid ceramic particles on a substrate using conventional TIG torch melting technique (known as hard face surfacing). Surface layers thickness from 0.05 to 1.0 mm is formed, which are characterized by the process variables of heat input, particles feed rate and gas flow rate. Typical operating conditions employ TIG input energies, preplaced particle amount, gas flow rate and working distance. The hybrid composite layer was investigated by a diversity of techniques, including optical microscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD) and Microhardness testing.